Health Beliefs associated with the follow-up of pap smear abnormalities among low-income women in Medellín, Colombia (2020)
The purpose of the study was to explore variables of the health belief model in relation to the follow-up of abnormal Pap smear among low-income women in Medellín, Colombia. Eight focus groups (62 women) were conducted according to age groups (25–45 and 46–69 years). The data were analyzed using content analysis. The participants perceived themselves as vulnerable, recognized the severity of the disease in terms of both its emotional and physical consequences, perceived the benefits of the follow-up, and mentioned cues to action, such as social support and the support of health entities. Perceived self-efficacy was compromised by health system barriers and by personal barriers, such as placing the needs of their children ahead of their own, fear, neglect, and the pain caused by the diagnostic and therapeutic procedures. Health education activities aimed at increasing the follow-up of abnormal Pap smears should consider psychological factors.